High-durability concrete and preparation method thereof
By using the sustained release mechanism of modified fibers and sodium peroxide in concrete, the compressive strength and permeability of concrete are improved, the problem of insufficient durability of concrete in school buildings is solved, and the safety and stability of the building is enhanced , extends service life.
Patent Information
- Application Number
- CN202411400848.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-10
AI Technical Summary
The lack of durability of concrete structures in school buildings leads to fall off the walls, posing safety hazards, especially in harsh environments, which significantly reduces the resistance to seepage, crack resistance and durability, which affects the stability and service life of the building.
High durability concrete formula is adopted, including 80-100 parts of cement, 30-50 parts of fly ash, 20-30 parts of steel slag, 400-600 parts of coarse aggregate, 200-300 parts of fine aggregate, 20-30 parts of silicon ash , 15-25 parts of lithium slag, 3-5 parts of admixture, 50-60 parts of water and 25-40 parts of modified fibers, the modified fibers are pressurized and impregnated in a low-boiling solvent by polylactic fibers to form porous Outsourcing the wall layer, slowly releasing sodium peroxide to activate mineral components, and improve compressive strength and permeability.
It significantly improves the compressive strength and permeability of concrete, extends the service life of the building, reduces cracks caused by erosion, enhances the safety and stability of the building, and reduces the risk of wall peeling.
Smart Images

Figure BDA0005075222450000091 
Figure BDA0005075222450000092 
Figure BDA0005075222450000101
Abstract
Description
Technical Field
[0001] The present invention relates to the field of construction, and more particularly, to a high-durability concrete and a preparation method thereof. Background Art
[0002] With the rapid development of education, the quality and safety of school buildings have received increasing attention. As the main material for school buildings, the performance of concrete is directly related to the stability and service life of the building. C30 concrete is usually used for general building structures such as floor slabs and walls of school buildings, which can meet most building load requirements. C40 concrete is more suitable for parts with higher strength requirements, such as load-bearing columns and beams of school buildings and the ground of large public activity venues.
[0003] However, in recent years, many school buildings have experienced wall peeling. This phenomenon is not only widely present in main buildings such as teaching buildings, dormitory buildings, and libraries, but also extends to ancillary facilities such as walls and playground stands. The peeling wall not only destroys the neatness and beauty of the building's appearance, but more importantly, the peeling wall may injure pedestrians or cause other accidental injuries, posing a safety hazard.
[0004] One of the factors that cause wall skin to fall off is that the exterior wall skin is usually attached to a concrete structure. If there are problems with the concrete structure itself, such as cracks, it will affect the stability of the wall skin and cause it to fall off. The durability of the concrete will also affect the state of the wall skin, especially as the years of use increase, the performance of the concrete gradually deteriorates, especially under harsh environmental conditions (such as high temperature, high humidity, freeze-thaw cycles, etc.), its impermeability, crack resistance and durability are significantly reduced, which will also cause cracks, peeling and even falling off on the surface of the wall attached to the concrete structure, affecting the safety and service life of the building.
[0005] Therefore, further improving the performance of concrete, especially its durability during long-term use, is of great significance to building safety. Summary of the invention
[0006] In order to ensure the improvement of concrete performance, especially durability, the present application provides a high-durability concrete and a preparation method thereof.
[0007] In a first aspect, the present application provides a high-durability concrete, which adopts the following technical solution: A high-durability concrete comprises the following raw materials in parts by weight: 80-100 parts of cement, 30-50 parts of fly ash, 20-30 parts of steel slag, 400-600 parts of coarse aggregate, 200-300 parts of fine aggregate, 20-30 parts of silica fume, 15-25 parts of lithium slag, 3-5 parts of admixture, 50-60 parts of water and 25-40 parts of modified fiber; The modified fiber is prepared by impregnating polylactic acid fiber in a low boiling point solvent under pressure, coating it with an inner coating layer, mixing it with sodium peroxide, coating it with an outer coating layer, and then forming a porous outer wall layer.
[0008] By adopting the above technical scheme, the polylactic acid fiber is added to the concrete, which has the characteristics of high strength and good ductility. It is added to the concrete to help improve its crack resistance and strength performance. More importantly, there are a few grooves, holes or cracks of varying depths on the surface of the polylactic acid fiber, which make it easy for the fiber to form a capillary effect, thereby showing very good wicking and diffusion phenomena. Because the polylactic acid fiber is curled, its product is relatively fluffy, and the wicking and diffusion effects of the polylactic acid fiber are very good. When the polylactic acid fiber is pressurized and impregnated in a low-boiling point solvent, due to the wicking of the polylactic acid fiber The polylactic acid fiber is loaded with a low boiling point solvent, and then coated with an inner coating layer, mixed with sodium peroxide, and then coated with an outer coating layer. When the modifier is added to the concrete for mixing, the outer coating layer slowly releases sodium peroxide, and the sodium peroxide decomposes to form sodium hydroxide and oxygen. Sodium hydroxide, as a mineral activator, can significantly improve the activation effect on fly ash and other mineral powders, release active ingredients such as aluminum oxide and silicon oxide, further participate in the cement hydration process, help fill the internal pores of the concrete, make the concrete more compact, and thus improve its compressive strength; The addition of the generated sodium hydroxide helps to reduce the chloride ion permeability of concrete, and sodium hydroxide can also react with calcium silicate in concrete to generate sodium silicate and calcium hydroxide. The above effects are all helpful to improve the strength performance of concrete, so that it has better impermeability and erosion resistance, so that slow-setting soil can better resist the penetration and erosion of harmful substances such as moisture and chemicals, maintain its long-term stability and durability, thereby increasing the service life of the building and reducing cracking caused by erosion; and the volatilization of low-boiling point solvents is an endothermic process, which also helps to reduce shrinkage cracks caused by excessively high cement hydration exothermic temperature; In addition, the addition of silica fume and the like in this application can reduce the alkali-aggregate reaction and prevent the formation of expansion products due to the alkali-aggregate reaction and cause cracking. The sodium peroxide microcapsule slow-release structure in this application not only realizes the mineral activation during the cement hydration process to improve its performance, but also the concrete usually bleeds after oxidation, which leads to a decrease in its strength and durability. The sodium peroxide added in this application helps to consume the above-mentioned excess water to generate sodium hydroxide, which then further reacts with the active substances of the mineral admixture to generate hydration products to further fill the internal pores and microcracks of the concrete, thereby improving the strength and durability. After the concrete is cured and hardened, the internal water accumulation due to the water absorption of the concrete, coupled with repeated thermal barriers and shrinkage, can also cause the concrete to crack. The residual sodium peroxide in this application will also react with the absorbed water to form sodium hydroxide, and the sodium hydroxide further hydrates with the cement to form hydration products to fill the pores, further improving the durability of the concrete.
[0009] Silica fume and lithium slag are also added in the present application to inhibit alkali-aggregate reaction. Lithium slag can reduce the Ca / Si ratio of hydration products in the system, and hydration products with low Ca / Si ratio have a strong ability to adsorb alkali ions, thereby reducing the corrosive effect of alkali on active aggregates, so that the sodium hydroxide generated in the modified fiber can activate minerals such as fly ash, thereby reducing the performance degradation caused by alkali-aggregate reaction.
[0010] Optionally, the low boiling point solvent is a combination of acetone and ether, dichloromethane or pentane. More preferably, the low boiling point solvent is a combination of acetone and pentane or dichloromethane.
[0011] By adopting the above technical scheme, when the above low-boiling point solvent is selected, during the concrete mixing process, the low-boiling point solvent evaporates due to the heat of concrete hydration, causing the inner coating layer to rupture, and at the same time, the outer coating layer is accelerated to rupture due to the volume change of the volatilized low-boiling point solvent, releasing sodium peroxide. The low-boiling point solvent plays an endothermic role in the volatilization process, thereby reducing the hydration heat and the probability of cracking due to temperature increase. At the same time, the released sodium peroxide also plays a role in activating fly ash.
[0012] Optionally, the modified fiber is prepared by the following method: 1) First, the polylactic acid fiber is impregnated in a low boiling point solvent under pressure, and then filtered to obtain the pretreated polylactic acid fiber; 2) dissolving polyurea and polyurethane in tetrahydrofuran to obtain a spray solution, spraying the spray solution on the surface of the pretreated polylactic acid fiber, and then mixing with sodium peroxide and granulating after standing to obtain a composite core material; 3) Mix hydroxypropyl beta-cyclodextrin with water, then add cerium stearate particles to obtain a wall material mixture, spray-dry the wall material mixture on a composite core material, and then wash it with benzene to obtain a modified fiber.
[0013] By adopting the above technical scheme, the present application first sprays polyurea and polyurethane solutions on the surface of the pretreated polylactic acid fiber, then mixes with sodium peroxide to form a composite core material, and then coats it to form an outer wall material mainly composed of hydroxypropyl β-cyclodextrin. Cerium stearate is insoluble in water but soluble in benzene. Therefore, in the present application, the above mixture is spray-dried on the composite core material, and then washed with benzene to elute the cerium stearate, thereby forming a porous wall material with a pore structure. Moreover, the wall material is mainly composed of hydroxypropyl β-cyclodextrin, which has a special three-dimensional ring structure that is hydrophobic inside and hydrophilic outside. After the wall material is coated on the composite core material, the compatibility of the polylactic acid fiber with concrete is improved, thereby improving its uniform dispersion in concrete, and improving strength and durability.
[0014] Optionally, when preparing the modified fiber, in step 1), when the polylactic acid fiber is immersed in a low boiling point solvent, the immersion time is 40-60 minutes and the immersion pressure is 1.2-1.8 MPa.
[0015] Optionally, when preparing the modified fiber, the polylactic acid fiber in step 1) is immersed in a low boiling point solvent; In step 2), the mass ratio of polyurea, polyurethane and tetrahydrofuran added is 1:(0.6-0.8):(0.8-1), the mass ratio of spray solution to pretreated polylactic acid added is 1:(2-2.5), and the mass ratio of sodium peroxide to polylactic acid fiber added is 1:(2-3); in step 3), the mass ratio of hydroxypropyl β-cyclodextrin to water added is 1:(0.7-0.9), the amount of cerium stearate particles added is 5-8wt% of hydroxypropyl β-cyclodextrin, and the mass ratio of wall material mixture to composite core material added is 1:(0.8-1.2).
[0016] Optionally, the concrete raw materials also include 10-20 parts of improvers, which include glass fiber tube B and hydrogen peroxide encapsulated in glass fiber tube B and glass fiber tube A, glass fiber tube A is encapsulated with a mixture of sodium peroxide, iron powder and ferric chloride, and the outer wall of glass fiber tube A and the inner wall of glass fiber tube B are coated with anti-corrosion coating.
[0017] By adopting the above technical solution, when cracks appear in concrete, the glass fiber tube A and the glass fiber tube B are broken, and the hydrogen peroxide in the glass fiber tube B is released, while the sodium peroxide, iron powder and ferric chloride in the glass fiber tube A are released. Under the action of the ferric chloride catalyst, the hydrogen peroxide decomposes to generate water and oxygen, and under the action of water, the sodium peroxide decomposes to generate sodium hydroxide and oxygen, and the iron powder reacts with oxygen to generate iron oxide. Since the density of iron oxide is lower than that of iron powder, the volume expands during the reaction, which can play a role in repairing cracks. In addition, the generated sodium hydroxide reacts with the ferric chloride to generate an iron hydroxide precipitate, and then the sodium hydroxide continues to react with the active ingredients in the concrete to generate a precipitate, thereby achieving the repair of the cracks and reducing the shedding of the building exterior wall due to concrete cracking.
[0018] Optionally, the mass ratio of sodium peroxide, iron powder and ferric chloride added to the glass fiber tube A is 1:(1.5-1.8):(1.8-2).
[0019] By adopting the above technical solution and selecting the encapsulated filler with the above mix ratio, the concrete finally obtained has better durability.
[0020] Optionally, the glass fiber tube A has a length of 5-6 mm and an inner diameter of 2-3 mm, while the glass fiber tube B has a length of 10-12 mm and an inner diameter of 5-6 mm.
[0021] Optionally, the admixture is a polycarboxylic acid water reducer and a cement alkali inhibitor in a mass ratio of 1:(0.1-0.2).
[0022] By adopting the above technical solution, a small amount of cement alkali inhibitor is added to the admixture in the present application to inhibit the alkali-aggregate reaction, thereby inhibiting the expansion and cracking of concrete caused by the alkali reaction problem.
[0023] In a second aspect, the present application provides a method for preparing high-durability concrete, which adopts the following technical solution: A method for preparing high-durability concrete comprises the following steps: S1, mixing cement, fly ash, coarse aggregate, fine aggregate, steel slag, lithium slag and silica fume, and then adding modified fiber to prepare a primary mixture; S2, mixing water and an additive, and then adding the preliminary mixture prepared in step S1, mixing and stirring to obtain the product.
[0024] By adopting the above technical solution, the concrete obtained by the method provided in this application has better durability, especially after being subjected to harsh environments such as high temperature, high humidity and freeze-thaw cycle conditions, the concrete has better long-term crack resistance and better durability.
[0025] Optionally, after the primary mixture is added and stirred to obtain a stirred mixture in step S2, 10-20 parts of a modifier are added, mixed and stirred to obtain a high-performance C30 / C40 concrete.
[0026] In summary, this application has the following beneficial effects: 1. In the present application, polylactic acid fibers with excellent wicking and diffusion properties are firstly impregnated in a low eutectic solvent under pressure, then coated with an inner coating layer, mixed with sodium peroxide, and then coated with an outer coating layer. When the modifier is added to the concrete for mixing, the outer wall layer slowly releases sodium peroxide, and the sodium peroxide decomposes to form sodium hydroxide and oxygen. Sodium hydroxide, as a mineral activator, can significantly improve the activation effect on fly ash and other mineral powders, release active ingredients such as aluminum oxide and silicon oxide, further participate in the cement hydration process, and help fill the internal pores of the concrete, making the concrete more compact, thereby improving its compressive strength. The generated sodium hydroxide helps to improve the strength performance of the concrete, thereby having better impermeability and erosion resistance, so that the slow-setting soil can better resist the penetration and erosion of harmful substances such as water and chemicals, maintain its long-term stability and durability, thereby improving the service life of the building and reducing cracking caused by erosion; and the volatilization of the low-boiling point solvent is an endothermic process, which also helps to reduce shrinkage cracks caused by excessively high cement hydration exothermic temperature; 2. The addition of the improver in the present application causes the glass fiber tube A and the glass fiber tube B to rupture when cracks appear in the concrete. The hydrogen peroxide in the glass fiber tube B is released, and the sodium peroxide, iron powder and ferric chloride in the glass fiber tube A are released. Under the action of the ferric chloride catalyst, the hydrogen peroxide decomposes to generate water and oxygen. Under the action of water, the sodium peroxide decomposes to generate sodium hydroxide and oxygen. The iron powder reacts with oxygen to generate iron oxide. Since the density of iron oxide is lower than that of iron powder, the volume expands during the reaction, which can play a role in repairing cracks. The generated sodium hydroxide reacts with the ferric chloride to generate an iron hydroxide precipitate, which is then combined with the sodium hydroxide to continue to react with the active ingredients in the concrete to generate a precipitate, thereby achieving the repair of the cracks and reducing the shedding of the building exterior wall due to concrete cracking. DETAILED DESCRIPTION
[0027] The present application is further described in detail below in conjunction with the examples. It is particularly noted that if no specific conditions are specified in the following examples, the experiments are carried out according to conventional conditions or the conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following examples can be obtained from common commercial sources.
[0028] The lithium slag in the following examples is industrial waste residue generated during the production of lithium salts such as lithium carbonate from spodumene by the sulfuric acid process; The anti-corrosion coating is KNM22 anti-corrosion coating produced by Beijing Naimer Technology Co., Ltd. The cement used is P.042.5 ordinary Portland cement; the fly ash used is FI grade fly ash; The coarse aggregate is crushed stone with a continuous particle size of 5-20 mm, and the fine aggregate is medium sand with a fineness modulus of 2.3-2.6; The polycarboxylate water reducer is the polycarboxylate water reducer model 0007 produced by Jinan Hongtai Chemical Co., Ltd.; The cement alkali inhibitor used is QC1711 cement alkali inhibitor.
[0029] The following preparation examples are preparation examples of modified fibers: Preparation Example 1 A method for preparing a modified fiber comprises the following steps: 1) First, the polylactic acid fiber is impregnated in a low boiling point solvent under pressure, and then filtered to obtain the pretreated polylactic acid fiber; The low boiling point solvent is obtained by mixing acetone and dichloromethane in a mass ratio of 1:2.5, and the low boiling point solvent is immersed in the polylactic acid fiber, the immersion time is 50 minutes, and the immersion pressure is 1.5 MPa; 2) dissolving polyurea and polyurethane in tetrahydrofuran, with the mass ratio of polyurea, polyurethane and tetrahydrofuran being 1:0.7:0.9, to obtain a spray solution, spraying the spray solution on the surface of the pretreated polylactic acid fiber, and then mixing with sodium peroxide and granulating after standing to obtain a composite core material; wherein the mass ratio of the spray solution to the pretreated polylactic acid is 1:2.2, and the mass ratio of the sodium peroxide to the polylactic acid fiber is 1:2.5; 3) Mix hydroxypropyl β-cyclodextrin and water in a mass ratio of 1:0.8, and then add cerium stearate particles, wherein the amount of cerium stearate particles added is 6wt% of hydroxypropyl β-cyclodextrin to obtain a wall material mixture, spray-dry the wall material mixture on a composite core material, and then wash with benzene and air-dry to obtain a modified fiber, wherein the mass ratio of the wall material mixture to the composite core material is 1:1.
[0030] Preparation Example 2 A method for preparing a modified fiber comprises the following steps: 1) First, the polylactic acid fiber is impregnated in a low boiling point solvent under pressure, and then filtered to obtain the pretreated polylactic acid fiber; The low boiling point solvent is obtained by mixing acetone and dichloromethane in a mass ratio of 1:2, and the low boiling point solvent is immersed in the polylactic acid fiber, the immersion time is 40 minutes, and the immersion pressure is 1.8 MPa; 2) dissolving polyurea and polyurethane in tetrahydrofuran, with the mass ratio of polyurea, polyurethane and tetrahydrofuran being 1:0.6:0.8, to obtain a spray solution, spraying the spray solution on the surface of the pretreated polylactic acid fiber, and then mixing with sodium peroxide and granulating after standing to obtain a composite core material; wherein the mass ratio of the spray solution to the pretreated polylactic acid is 1:2, and the mass ratio of the sodium peroxide to the polylactic acid fiber is 1:2; 3) Mix hydroxypropyl β-cyclodextrin and water in a mass ratio of 1:0.7, then add cerium stearate particles, the amount of cerium stearate particles added is 5wt% of hydroxypropyl β-cyclodextrin, to obtain a wall material mixture, spray-dry the wall material mixture on a composite core material, and then wash with benzene and air-dry to obtain a modified fiber, wherein the mass ratio of the wall material mixture to the composite core material is 1:0.8.
[0031] Preparation Example 3 A method for preparing a modified fiber comprises the following steps: 1) First, the polylactic acid fiber is impregnated in a low boiling point solvent under pressure, and then filtered to obtain the pretreated polylactic acid fiber; The low boiling point solvent is obtained by mixing acetone and dichloromethane in a mass ratio of 1:3, and the low boiling point solvent is immersed in the polylactic acid fiber, the immersion time is 60 minutes, and the immersion pressure is 1.2 MPa; 2) dissolving polyurea and polyurethane in tetrahydrofuran, with the mass ratio of polyurea, polyurethane and tetrahydrofuran being 1:0.8:1, to prepare a spray solution, spraying the spray solution on the surface of the pretreated polylactic acid fiber, and then mixing with sodium peroxide and granulating after standing to prepare a composite core material; wherein the mass ratio of the spray solution to the pretreated polylactic acid is 1:2.5, and the mass ratio of the sodium peroxide to the polylactic acid fiber is 1:3; 3) Mix hydroxypropyl β-cyclodextrin and water in a mass ratio of 1:0.9, then add cerium stearate particles, the amount of cerium stearate particles added is 8wt% of hydroxypropyl β-cyclodextrin, to obtain a wall material mixture, spray-dry the wall material mixture on a composite core material, and then wash with benzene and air-dry to obtain a modified fiber, wherein the mass ratio of the wall material mixture to the composite core material is 1:1.2.
[0032] Preparation Example 4 A method for preparing a modified fiber is carried out according to the method in Preparation Example 1, except that in step 2), the low boiling point solvent is obtained by mixing acetone and pentane in a mass ratio of 1:2.5. Comparative Preparation Example 1 A method for preparing modified fiber is carried out according to the method in Preparation Example 1, except that cerium stearate is not added in step 3).
[0033] Example 1 A method for preparing high-durability concrete comprises the following steps: S1, 90 kg of cement, 40 kg of fly ash, 500 kg of coarse aggregate, 250 kg of fine aggregate, 25 kg of steel slag, 20 kg of lithium slag and 25 kg of silica fume were mixed and stirred, and then 30 kg of the modified fiber prepared in Preparation Example 1 was added to prepare a primary mixture; S2, 55kg of water and 4kg of admixture are mixed, and then the primary mixture prepared in step S1 is added, and the mixture is mixed and stirred to prepare high-performance C30 / C40 concrete; wherein the admixture is a polycarboxylate water reducer and a cement alkali inhibitor in a mass ratio of 1:0.15.
[0034] Example 2 A method for preparing high-durability concrete comprises the following steps: S1, 80kg of cement, 30kg of fly ash, 400kg of coarse aggregate, 200kg of fine aggregate, 20kg of steel slag, 15kg of lithium slag and 20kg of silica fume were mixed and stirred, and then 25kg of the modified fiber prepared in Preparation Example 2 was added to prepare a primary mixture; S2, 50kg of water and 3kg of admixture are mixed, and then the primary mixture prepared in step S1 is added, and the mixture is mixed and stirred to obtain high-performance C30 / C40 concrete; wherein the admixture is a polycarboxylate water reducer and a cement alkali inhibitor in a mass ratio of 1:0.1.
[0035] Example 3 A method for preparing high-durability concrete comprises the following steps: S1, 100 kg of cement, 50 kg of fly ash, 600 kg of coarse aggregate, 300 kg of fine aggregate, 30 kg of steel slag, 25 kg of lithium slag and 30 kg of silica fume were mixed and stirred, and then 40 kg of the modified fiber prepared in Preparation Example 3 was added to prepare a primary mixture; S2, 60kg of water and 5kg of admixture are mixed, and then the primary mixture prepared in step S1 is added, and the mixture is mixed and stirred to prepare high-performance C30 / C40 concrete; wherein the admixture is a polycarboxylate water reducer and a cement alkali inhibitor in a mass ratio of 1:0.2.
[0036] Example 4 A method for preparing high-durability concrete is carried out according to the method in Example 1, except that the modified fiber is the modified fiber prepared in Preparation Example 4.
[0037] Example 5 A method for preparing high-durability concrete is carried out according to the method in Example 1, except that, in step S2, a primary mixture is added to obtain a stirred mixture; and then step S3 is further carried out: 15 kg of a modifier is added to the stirred mixture in step S2, and the mixture is mixed and stirred to obtain high-performance C30 / C40 concrete; Wherein, the improver in step S3 is prepared by the following method: Firstly, sodium peroxide, iron powder and ferric chloride are mixed in a mass ratio of 1:1.6:1.9 and then packaged in a glass fiber tube A, wherein the length of the glass fiber tube A is 5 mm and the inner diameter is 2 mm; Then, the outer wall of the glass fiber tube A is coated with an anti-corrosion coating and then dried and cured at low temperature. At the same time, the inner wall of the glass fiber tube B is also sprayed with an anti-corrosion coating and then dried and cured at low temperature. The length of the glass fiber tube B is 11 mm and the inner diameter is 5 mm. Then, the glass fiber tube A and hydrogen peroxide are co-encapsulated in a glass fiber tube B sprayed with an anti-corrosion coating according to a volume ratio of 6:3, and the volume of the glass fiber tube A and hydrogen peroxide in the glass fiber tube B accounts for 90% in total, thereby preparing a modifier.
[0038] Example 6 A method for preparing high-durability concrete is carried out according to the method in Example 1, except that, in step S2, a primary mixture is added to obtain a stirred mixture; and then step S3 is further carried out: 10 kg of a modifier is added to the stirred mixture in step S2, and the mixture is mixed and stirred to obtain high-performance C30 / C40 concrete; Wherein, the improver in step S3 is prepared by the following method: Firstly, sodium peroxide, iron powder and ferric chloride are mixed in a mass ratio of 1:1.5:1.8 and then encapsulated in a glass fiber tube A, wherein the length of the glass fiber tube A is 5 mm and the inner diameter is 2 mm; Then, the outer wall of the glass fiber tube A is coated with an anti-corrosion coating and then dried and cured at low temperature. At the same time, the inner wall of the glass fiber tube B is also sprayed with an anti-corrosion coating and then dried and cured at low temperature. The length of the glass fiber tube B is 10 mm and the inner diameter is 5 mm. Then, the glass fiber tube A and hydrogen peroxide are co-encapsulated in a glass fiber tube B sprayed with an anti-corrosion coating according to a volume ratio of 6:3, and the volume of the glass fiber tube A and hydrogen peroxide in the glass fiber tube B accounts for 90% in total, thereby preparing a modifier.
[0039] Example 7 A method for preparing high-durability concrete is carried out according to the method in Example 1, except that, in step S2, a primary mixture is added to obtain a stirred mixture; and then step S3 is further carried out: 20 kg of a modifier is added to the stirred mixture in step S2, and the mixture is mixed and stirred to obtain; Wherein, the improver in step S3 is prepared by the following method: Firstly, sodium peroxide, iron powder and ferric chloride are mixed in a mass ratio of 1:1.8:2 and then encapsulated in a glass fiber tube A, wherein the length of the glass fiber tube A is 6 mm and the inner diameter is 3 mm; Then, the outer wall of the glass fiber tube A is coated with an anti-corrosion coating and then dried and cured at low temperature. At the same time, the inner wall of the glass fiber tube B is also sprayed with an anti-corrosion coating and then dried and cured at low temperature. The length of the glass fiber tube B is 12 mm and the inner diameter is 6 mm. Then, the glass fiber tube A and hydrogen peroxide are co-encapsulated in a glass fiber tube B sprayed with an anti-corrosion coating according to a volume ratio of 6:3, and the volume of the glass fiber tube A and hydrogen peroxide in the glass fiber tube B accounts for 90% in total, thereby preparing a modifier.
[0040] Example 8 A method for preparing high-durability concrete is carried out according to the method in Example 1, except that in step S3, the ferric chloride in the glass fiber tube A of the improver is replaced by sodium peroxide and iron powder in a mass ratio of 1:1.6.
[0041] Comparative Example 1 A method for preparing high-durability concrete is carried out according to the method in Example 1, except that the modified fiber is the modified fiber prepared in Comparative Preparation Example 1.
[0042] Comparative Example 2 A method for preparing high-durability concrete is carried out according to the method in Example 1, except that no modified fiber is added in step S1.
[0043] Comparative Example 3 A method for preparing high-durability concrete is carried out according to the method in Example 1, except that the modified fiber in step S1 is replaced by polylactic acid fiber in equal amounts.
[0044] Comparative Example 4 A method for preparing high-durability concrete is carried out according to the method in Example 1, except that lithium slag is not added in step S1.
[0045] Performance Testing The concrete prepared in this application was tested for 28d compressive strength, and the test results are shown in Table 1. In addition, the concrete test blocks (100mm×100mm×100mm) with an age of 28d were first saturated with water, and then each test piece was subjected to 100 freeze-thaw treatments according to the slow freezing method of "KGB / T50082-2009 Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete", and then placed at 35°C and 80% humidity for 18d. The compressive strength loss rate of the test pieces after the above treatment was counted, and the total crack area after the above treatment was counted. The statistical results are shown in Table 2.
[0046] Table 1: Referring to the test results in Table 1 above, the concrete prepared in the examples of the present application has good compressive strength.
[0047] Table 2: Referring to the test results in Table 2 above, the concrete test block prepared in the embodiment of the present application was subjected to a long freeze-thaw cycle by the slow freezing method, and was also treated in a high temperature and high humidity environment. The compressive strength loss of the prepared concrete was small. Combining the test results of Example 1 and Example 4, when acetone and pentane were used as the low boiling point solvents in the modified fiber in Example 4, its durability was reduced compared to the combination of acetone and dichloromethane. Combining the test results of Example 1 and Examples 5-7, it can be seen that when a modifier is added to the concrete raw material, the durability of the concrete is significantly improved. Combined with the test results of Example 8, when ferric chloride is not added to the modifier in Example 8, its durability is significantly reduced. Ferric chloride cannot act as a catalyst and cannot form a precipitate with sodium hydroxide to repair cracks, which reduces the durability of the concrete.
[0048] Referring to the test results of Example 1 and Comparative Example 1, when the outer wall material of the modified fiber in Comparative Example 1 did not form a porous structure, the compressive strength and durability of the concrete were significantly reduced. Combined with the test results of Comparative Examples 2 and 3, when no modified fiber was added in Comparative Example 2, its durability and compressive strength were significantly reduced. When only polylactic acid fiber was added to the concrete in Comparative Example 3, its durability and strength were improved compared with Comparative Example 2, but still far weaker than Example 1. Referring to the test results of Comparative Example 4, when lithium slag was not added to the concrete raw materials, its compressive strength and durability were reduced, which may be because lithium slag can inhibit the performance loss caused by the reduction of alkali-aggregate reaction.
[0049] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A high durability concrete, characterized in that: It includes the following raw materials in parts by weight: 80-100 parts of cement, 30-50 parts of fly ash, 20-30 parts of steel slag, 400-600 parts of coarse aggregate, 200-300 parts of fine aggregate, 20-30 parts of silica fume, 15-25 parts of lithium slag, 3-5 parts of admixtures, 50-60 parts of water and 25-40 parts of modified fiber; The modified fiber is prepared by impregnating polylactic acid fiber in a low boiling point solvent under pressure, coating it with an inner coating layer, mixing it with sodium peroxide, coating it with an outer coating layer, and then forming a porous outer wall layer.
2. The high-durability concrete according to claim 1, characterized in that: The low boiling point solvent is a combination of acetone and ether, dichloromethane or pentane.
3. The high-durability concrete according to claim 1, characterized in that: The modified fiber is prepared by the following method: 1) First, the polylactic acid fiber is impregnated in a low boiling point solvent under pressure, and then filtered to obtain the pretreated polylactic acid fiber; 2) Dissolve polyurea and polyurethane in tetrahydrofuran to prepare a spray solution, spray the spray solution on the surface of the pretreated polylactic acid fiber, and then mix it with sodium peroxide and granulate it after standing to prepare a composite core material; 3) Mix hydroxypropyl beta-cyclodextrin with water, then add cerium stearate particles to obtain a wall material mixture, spray-dry the wall material mixture on a composite core material, and then wash it with benzene to obtain a modified fiber.
4. The high-durability concrete according to claim 1, characterized in that: When preparing the modified fiber, in step 1), when the polylactic acid fiber is immersed in the low boiling point solvent, the immersion time is 40-60 minutes and the immersion pressure is 1.2-1.8 MPa.
5. The high-durability concrete according to claim 3, characterized in that: When preparing the modified fiber, in step 1), the polylactic acid fiber is immersed in a low boiling point solvent; In step 2), the mass ratio of polyurea, polyurethane and tetrahydrofuran is 1:(0.6-0.8):(0.8-1), the mass ratio of spray solution to pretreated polylactic acid is 1:(2-2.5), and the mass ratio of sodium peroxide to polylactic acid fiber is 1:(2-3); In step 3), the mass ratio of hydroxypropyl β-cyclodextrin to water is 1:(0.7-0.9), the amount of cerium stearate particles added is 5-8wt% of hydroxypropyl β-cyclodextrin, and the mass ratio of the wall material mixture to the composite core material is 1:(0.8-1.2).
6. The high-durability concrete according to claim 1, characterized in that: The concrete raw materials also include 10-20 parts of improvers, which include glass fiber tube B, hydrogen peroxide encapsulated in the glass fiber tube B, and glass fiber tube A, a mixture of sodium peroxide, iron powder and ferric chloride is encapsulated in the glass fiber tube A, and the outer wall of the glass fiber tube A and the inner wall of the glass fiber tube B are coated with anti-corrosion coatings.
7. The high-durability concrete according to claim 6, characterized in that: The mass ratio of sodium peroxide, iron powder and ferric chloride added in the glass fiber tube A is 1:(1.5-1.8):(1.8-2).
8. The high-durability concrete according to claim 6, characterized in that: The glass fiber tube A has a length of 5-6 mm and an inner diameter of 2-3 mm, while the glass fiber tube B has a length of 10-12 mm and an inner diameter of 5-6 mm.
9. The high-durability concrete according to claim 1, characterized in that: The admixture is a polycarboxylic acid water reducer and a cement alkali inhibitor in a mass ratio of 1: (0.1-0.2).
10. The method for preparing high performance C30 / C40 concrete according to any one of claims 1 to 9, characterized in that: The following steps are involved: S1, mixing cement, fly ash, coarse aggregate, fine aggregate, steel slag, lithium slag and silica fume, and then adding modified fiber to prepare a primary mixture; S2, mixing water and an additive, and then adding the preliminary mixture prepared in step S1, mixing and stirring to obtain the product.